2017
DOI: 10.1097/psy.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subjective Well-being on Mortality: A Meta-Analysis of Longitudinal Studies in the General Population

Abstract: Our results suggest that subjective well-being is associated with a decreased risk of mortality. Longitudinal studies examining changing levels of well-being and their relationship to longevity would be required to establish a cause-effect relationship. Establishing such a causal relationship would strengthen the case for policy interventions to improve the population subjective well-being to produce longevity gains combined with optimizing quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 51 publications
8
113
2
2
Order By: Relevance
“…Considering the close relationship between subjective psychological well-being and health, this connection becomes particularly important while aging, when the prevalence of chronic illness increases. In this respect, high levels of SPWB have been associated with a decreased risk in mortality in general [55,56]. Interestingly, in in our study sample, resilience did not correlate with number of diseases.…”
Section: Discussioncontrasting
confidence: 51%
“…Considering the close relationship between subjective psychological well-being and health, this connection becomes particularly important while aging, when the prevalence of chronic illness increases. In this respect, high levels of SPWB have been associated with a decreased risk in mortality in general [55,56]. Interestingly, in in our study sample, resilience did not correlate with number of diseases.…”
Section: Discussioncontrasting
confidence: 51%
“…Life satisfaction is generally measured by asking respondents how satisfied they feel in their life, placing themselves in a given point on a given scale [10]. The eudemonic concept of wellbeing is focused on meaning and purpose in life and self-realization, and it defines wellbeing in terms of the degree to which people feel fulfilled as they function in different areas of life [12]. Eudemonic wellbeing emphasizes the importance of psychological constructs such as personal meaning and growth [8,13,14], which are usually measured through structured self-reported scales focused on multiple dimensions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Eudemonic wellbeing emphasizes the importance of psychological constructs such as personal meaning and growth [8,13,14], which are usually measured through structured self-reported scales focused on multiple dimensions [14,15]. The hedonic wellbeing approach defines wellbeing in terms of pleasure and pain [12], considering feelings such as happiness, sadness, anger, stress and pain. It is commonly measured by analyzing positive and negative experiences in people's daily lives with experience sampling methodologies (ESM) or similar methods based on diary techniques to appraise subjective experiences in daily life such as the day reconstruction method [6,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis suggests that SWB is associated with a decreased risk in mortality in general [8]. Research on the determinants of SWB among older adults has identified social relationships [9], social capital [10], socioeconomic status [11] and psychosocial resources [12] as major factors.…”
Section: Introductionmentioning
confidence: 99%